Case Report: Overlap syndrome of relapsing polychondritis and systemic lupus erythematosus observed in women: a comprehensive review and unique case presentation - Bustos-Merlo, Antonio; Navarrete-Navarrete, Nuria; González-Navarrete, Lourdes; Martín-Armada, María (Frontiers in Lupus, 2024)
Relapsing polychondritis (RP) is an immune-related condition involving inflammation of cartilaginous structures and other body tissues, especially affecting the ears, nose, eyes, joints and respiratory tract. Approximately one-third of patients with RP have an identifiable form of systemic vasculitis, connective tissue disease, other autoimmune disease, or a malignant or premalignant condition. In this report, we present the case of a 50-year-old woman who met criteria for systemic lupus erythematosus (SLE) and was diagnosed with RP several months later.The main objective was to investigate cases of overlap syndrome involving RP and SLE. A literature review of reported cases with this coexistence was conducted, examining presentation, predominant symptoms, laboratory data, complications and systemic involvement. The review included a total of 12 cases of overlap syndrome of RP and SLE, analysing the epidemiology, temporal relationship, clinical features, diagnosis, treatment and evolution of the reported cases.Although this overlapping presence is rare (less than 1%), it emphasises the importance of maintaining a high index of suspicion for RP in patients with SLE who present with recurrent episodes of scleritis, audiovestibular involvement and chondritis.